Fractionation and activity assay of the root extract of Piper sarmentosum Roxb. ex Hunter against Candida albicans - Hartiwi Diastuti; Sadijah Achmad; Enny Ratnaningsih (Indonesian Journal of Pharmacy, 2004)
Piper sarmentosum Roxb. ex Hunter (“sirih duduk”) has long been used as a traditional medicine against fungoid diseases, especially at vagina and foot-sole. The investigation of the bioactive compounds of P. sarmentosum roots has not infections been carried yet. This research was then aimed to fractinate and to examine the antifungus activity of the extract of P. sarmentosum roots.The extraction was performed by using organic solvents such as methanol, ethyl acetate, chloroform, benzene, and n-hexane. The bioactivity tests were performed against C. albicans. The active extracts were then fractionated by coloumn chromatography.The result showed that the ethyl acetate fraction of methanol extract of P. sarmentosum roots have an antifungus activity against C. albicans. Phytochemical study showed that the active fractions of the methanol extracts of P. sarmentosum roots contained alkaloid.Key words : Piper sarmentosum, activity test, Candida albicans.